Leonor in dance the life, the legend and the lore - De la Cruz, Libertine Santos; Froilan, Nonoy; Vida, Edna (Kuwadro, 2002)
Leonor Orosa Goquingco, a pioneer choreographer in stylized Philippine ballet theater for over four decades, confronted the challenge of elevating Philippine dance to high creative art, lifting it to its peak of national artistic development. Her works are classics of the dance, and her most important works - Vinta, Trend, Return to Native, Noli Dance Suite, Filipinescas: Philippine Life, Legend and Lore in Dance are among her most vital contribution to the art of Philippine dance. She was named National Artist for Creative Dance in 1976 for her pioneering efforts and achievements in the art of choreography.